(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Unions are moral persons, who acquire legal personality by registering with the competent labor authority and which exercise economic and patrimonial resources in fulfillment of their interests for the benefit of the worker base, for which they are bound by the Labor Law in conjunction with the General Law of Transparency and Access to Public Information, to publish all the information related to its registration and its actions, as well as to render a report to its members on the use of union assets and the fees that are deducted from their salaries, which we will analyze in an analytical and propositional way, through legal realism.